Heavy metal removal from solutions using metallic iron. (1st July 2013) - Gylienė, O; Grincienė, G; Verbickas, R; Butkienė, R; Misiūnas, A; Vitėnienė, I
Abstract : Metallic iron enables an effective heavy metal removal from the single Cu(II), Cr(VI), Zn(II), Ni(II), Pb(II) and Cd(II) solutions and from their mixture under batch conditions and in the flow mode. The kinetic experiments of metal removal and analysis of precipitate formed indicated a more complicated mechanism of the decontamination process as compared to that of ordinary reduction of metal ions with metallic iron. Chemical, FTIR and X-ray analyses of the precipitate show its chemical change with time. Metal ions in solutions were determined using chemical analysis and anodic stripping voltammetry with the bismuth film electrode.